Analisis Daya Saing Sektor Ekonomi Unggulan Di Kabupaten Tangerang Tahun 2013-2022 - Prabowo, Yanuar (Jurnal Ilmu Ekonomi JIE, 2023)
This research aims to identify and evaluate the key economic sectors with development potential in the second-level region of Tangerang during the period 2011-2022. The research conducted is of a descriptive nature, utilizing ADHK GDP distribution data. Data analysis is performed through the employment of Tipology Klassen, Shift Share, SLQ, and DLQ methods. The research findings indicate that, during the period from 2013 to 2022, three sectors experienced significant growth, namely Agriculture, Forestry, and Fisheries, Manufacturing Industry, and Electricity and Gas Supply. Furthermore, the Shift Share analysis identified that the Wholesale and Retail Trade sector exhibited a high level of competitiveness during the same period. The combined analysis of SLQ and DLQ during the same period revealed that the leading economic sectors in the second-level region of Tangerang are Construction and Financial and Insurance Services.   Penelitian ini bertujuan untuk mengidentifikasi dan mengevaluasi sektor ekonomi utama yang memiliki potensi pengembangan di Kabupaten Tangerang dalam periode 2011-2022. Jenis penelitian yang digunakan adalah penelitian deskriptif, dengan menggunakan data distribusi PDRB ADHK. Analisis data dilakukan dengan menggunakan metode Tipologi Klassen, Shift Share, SLQ, dan DLQ. Hasil penelitian menunjukkan bahwa dalam periode 2013-2022, ada tiga sektor yang mengalami pertumbuhan signifikan, yaitu Pertanian, Kehutanan, dan Perikanan, Industri Pengolahan, serta Pengadaan Listrik dan Gas. Selain itu, analisis Shift Share mengidentifikasi bahwa sektor Perdagangan besar dan eceran memiliki tingkat daya saing yang tinggi dalam periode yang sama. Hasil gabungan analisis SLQ dan DLQ dalam periode yang sama mengungkapkan bahwa sektor ekonomi unggulan di Kabupaten Tangerang adalah Konstruksi dan Jasa Keuangan serta Asuransi